(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, Hamza Hakimzade Niazi was known as the author of lyrical poems, educational books and dramas. At the same time, it is shown that after the establishment of Soviet power in our country, he became a fighter and propagandist of the ideology of Soviet power, and for many years after his death he was falsely valued by high definitions such as "the founder of Uzbek Soviet literature and culture." That is, at the heart of such a policy, cunning and political ideas are highlighted that a writer and intellectual from the local people should serve socialism and the leaders in the center with such loyalty.